Blockchain-Based Anonymous Reputation System for Performance Appraisal - Hye Jin Lee; Duc Anh Luong; Jong Hwan Park; Hyoseung Kim (IEEE Access)
Performance appraisal is crucial in human resource management to identify areas within organizations. Ensuring anonymity and confidentiality is important to obtain honest feedback and prevent retaliation. Although blockchain-based anonymous reputation systems have been discussed, permissioned blockchains are susceptible to Sybil attack vulnerabilities, while permissionless private blockchains do not provide full anonymity. We present the Anonymous Reputation System for Performance Appraisal (ARSPA), which uses a permissionless public blockchain. This system is designed for upward feedback in performance appraisals, employing cryptographic techniques such as non-interactive zero-knowledge proofs, public key encryption, and Merkle trees to ensure security. Our protocol addresses the risks of Sybil attacks, ensures review limitation and unforgeability. We validate the security of ARSPA through analysis and demonstrate its feasibility through proof-of-concept on Ethereum test networks. ARSPA provides a secure and efficient approach to improve the reliability and fairness of performance appraisal.